2004
DOI: 10.1073/pnas.0405887101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mushroom body miniature, a zinc-finger protein implicated in brain development of Drosophila

Abstract: The mushroom bodies are bilaterally arranged structures in the protocerebrum of Drosophila and most other insect species. Mutants with altered mushroom body structure have been instrumental not only in establishing their role in distinct behavioral functions but also in identifying the molecular pathways that control mushroom body development. The mushroom body miniature 1 (mbm 1 ) mutation results in grossly reduced mushroom bodies and odor learning deficits in females. With a survey of genomic rescue constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…However, unlike other known transcription factors carrying the C 2 H 2 zinc finger, NsdC possesses an additional C 2 HC motif comprising 80 amino acid residues that is highly conserved in various fungal species ( Figure 1B). The C 2 HC motif is found in various eukaryotic proteins that have diverse functions such as chromatin acetylation (Akhtar and Becker 2001;Smith et al 2005), DNA repair ( Jones et al 1988), and development control (Raabe et al 2004;Xie et al 2005). Many C 2 HC motifs bind to DNA (Lee et al 1998;Simpson et al 2003) or interact with motifs of other transcription factors (Sadowski et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike other known transcription factors carrying the C 2 H 2 zinc finger, NsdC possesses an additional C 2 HC motif comprising 80 amino acid residues that is highly conserved in various fungal species ( Figure 1B). The C 2 HC motif is found in various eukaryotic proteins that have diverse functions such as chromatin acetylation (Akhtar and Becker 2001;Smith et al 2005), DNA repair ( Jones et al 1988), and development control (Raabe et al 2004;Xie et al 2005). Many C 2 HC motifs bind to DNA (Lee et al 1998;Simpson et al 2003) or interact with motifs of other transcription factors (Sadowski et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The transfection procedure for Western blots was essentially the same, except that 5 ϫ 10 6 S2 cells were transfected with 10 g dsRNA in single wells of a 6-well plate. Samples for Western blots were harvested and further processed according to standard procedures, using rabbit anti-Mbm (1:160) (22), mouse anti-Myc (1:50) (30), and mouse anti-␣-tubulin (1:5,000) (Sigma) antibodies for enhanced chemiluminescence (ECL) detection. For proliferation assays, a CellTrace CFSE cell proliferation kit (Molecular Probes) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Homology searches provided no clue about the molecular function of Mbm. Structural features of Mbm include several stretches enriched in certain amino acids, a putative nuclear localization signal, and two consecutive CCHC zinc knuckles (22). In this report, we describe Mbm as a new nucleolar protein.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…To verify these initial observations, we used the anti-Leo antibody, which is highly preferential for most adult MB neurons (Skoulakis and Davis, 1996;Crittenden et al, 1998;Raabe et al, 2004). Serial sections from heads of htau 0N4R -expressing animals from independent crosses revealed that all brains displayed defective MBs (Fig.…”
Section: Ablation Of the Mushroom Bodies Upon Pan-neuronal Accumulatimentioning
confidence: 99%